Determinantes da liquidez bancária na economia brasileira pós-acordos da Basiléia : 1996-2009 - Silva, Vinicius Oliveira (2009)
This research aims to analyze the main impacts of implementing the requirements of the Basel Accords on the liquidity of the National Banking System. These agreements resulted from shortages of liquidity and solvency of banks in the International Financial System, reflecting in all countries, demonstrating the widespread bank insolvency and banking risks. The prudential regulation undertaken by the Brazilian Banking Supervisor for the implementation of the Principles and Pillars of the Basel Accord, which provides best practice to combat financial problems brought greater solvency to banks in Brazil, and consolidated the industry by providing greater security for staff economic market participants. The soundness of the banking sector reduces risks. Thus, empirical research aims to identify the determinant variables of liquidity in the banking sector, which may be subject to policies to reduce the risk of illiquidity. These variables were calculated using the balance sheet of the top 12 domestic banks, Central Bank Ranking 2007. The application of VAR models, Vector Auto Regressive, points to the Selic rate to increase as positive bank liquidity, encouraging people to save, the IPCA is a negative liquidity, because people will use more resources to buy the same goods, the increase in efficiency Operational causes a decrease in liquidity, the bank can perform more operations in need of less liquidity, are another highlight of the derivatives that had a significant increase in operations, generating higher returns for banks.